2017
DOI: 10.7717/peerj.3527
|View full text |Cite
|
Sign up to set email alerts
|

An observational descriptive survey of rosacea in the Chinese population: clinical features based on the affected locations

Abstract: BackgroundThere is currently no study that has evaluated the differences in epidemiological and clinical characteristics among rosacea patients according to different facial sites.MethodsClinical and demographic data were obtained from 586 rosacea patients. The patients were divided into four groups based on the main sites involved with the rosacea lesions (full-face, cheeks, nose, or perioral involvement). Clinical signs were measured through self-reported, dermatologist-evaluated grading of symptoms, and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 30 publications
2
40
2
2
Order By: Relevance
“…In general, a wide range of skin capacitance values was reported (16·5–381·6 a.u.). Case–control studies demonstrated that skin hydration in patients with ETR and PPR was significantly lower than in controls . Moreover, Kim et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, a wide range of skin capacitance values was reported (16·5–381·6 a.u.). Case–control studies demonstrated that skin hydration in patients with ETR and PPR was significantly lower than in controls . Moreover, Kim et al .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies found normal sebum levels and skin surface lipid composition in patients compared with controls, and no correlation with disease severity or rosacea subtype existed . Two case–control studies found lower than normal skin surface lipids in patients with PPR, and another higher oil levels in patients with nasal rosacea . A fourth study showed significant differences in lipid composition on the back of patients (Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations